Ergodic capacity of dual-hop fixed gain relaying systems over mixed multipath/shadowing channels - Weijun Cheng (2014 Sixth International Conference on Wireless Communications and Signal Processing (WCSP), 2014)
The ergodic capacity of dual-hop fixed gain wireless communication systems is investigated under mixed fading environment. In such environment, the wireless links of relaying system undergo mixed multipath/shadowing fading conditions, where one link is subject to the Nakagami-m fading, the other link is subject to the composite Nakagami-lognormal fading which is approximated by using mixture gamma fading model. Novel closed-form expressions of the ergodic capacity for the considered system are derived, including the exact capacity expression and the capacity bounds. Numerical and simulation results are shown and discussed to verify the accuracy of the analytical results under different scenarios, such as varying average signal-to-noise ratio, fading parameters per hop, the gain constant and the location of relaying node.